Sensitivity analysis of simplified low cost converging thermal wave technique for thin bilayer solid - M. Shahril Shahril Bin Husin (International Journal of Advances in Applied Sciences, 2014)
In this paper, the sensitivity analysis of thermo physical parameters of the semi-infinite bilayer was presented by using a simplified converging thermal wave model. This is done under the consideration that radial flow of converging thermal wave substantially dominates in the first layer and axial thermal wave, dominates in the second layer. The sensitivity of the correlated parameters due to the 5%, 10% and 100% of increment were evaluated.. The results of the calculated temperature were simulated by Mathematica software, in order to generate a sensitivity analysis and examined by graphs. From this analysis, we concluded the optimum conditions, hence to be applied in the real experiment. Our merit on this report is for introducing a simple method of optical transient heating by using low cost equipment such as camera’s flash lamp and thermocouple, which may also apply to the short pulse laser measurement. A brief theory of the present work is presented and the results obtained from the simulation are discussed.